PAHAM AHLU SUNNAH WAL JAMA’AH DAN TANTANGAN KONTEMPORER DALAM PEMIKIRAN DAN GERAKAN ISLAM DI INDONESIA - Ahmad Syafi’i Mufid (Harmoni, 2013)
Literally , Ahlussunnah wal Jamaah are adherents of tradition and custom done by the Prophet Muhammad and the consensus of the scholars . Ahlussunnah wal Jamaah are the majority of Indonesian moslem. The character of moderation ( washatiyah ) owned by this school of thought, wheather the belief system (Aqeedah), Shari’ah and practice of moral / Sufism are in accordance with the pattern cultural patterns of Indonesian society . The dynamic of Ahlussunnah wal Jamaah development , initially assessed accommodative to the old traditions ( local tradition ) , but then following the trend of puritanical style then Islamic character looks more pure . Purification of Ahlussunnah wal Jamaah teachings from the local element and old traditions causing the birth of the modernist movement rests on the principles of thinking or istimbat al hukmi prevailing in these schools of thought. Social change as a result of development and encounters with various global thinking , Ahlussunnah wal Jamaah facing the challenges both internal and external. Could Ahlussunnah wal Jamaah able to put themselves in the position of moderate ( washatiyah ) in the midst of the onslaught of radicalism , liberalism and misguided thought (cult)?